(untitled) (World Economics and Finance Bulletin, 2023)
Traditional cost and administrative accounting systems have become unable to cope with the changes of the modern business environment. This ultimately led to the weakening of the competitive and financial performance of economic units, which in turn led to the search for alternative techniques and methods to those accounting systems that are no longer able to develop and improve the performance of economic units. Therefore, this research aims to highlight the role of Attribute Based Costing System (ABCII) as a modern strategic approach to improve performance through the appropriate and comprehensive information provided by this technology. This is in order to help economic units to optimize the use of resources, choose the appropriate combination of production and calculate the most accurate cost of the product, which contributes to improving the operational, competitive and financial performance of Al-Al-Narjes Company for Pipe Production. This is done by using its cost and financial data and relying on field visits and interviews with the engineering and administrative staff of the company to apply Attribute Based Costing System. The results of the research showed that the application of ABCII technology leads to improving the competitive and financial performance of the company, and it is clear that the performance improvement by reducing the cost of the product by (21) dollars was when using traditional systems. The researchers recommended the need for the company to, in the production of pipes, rely on modern management and cost methods and techniques, including ABCII technology because of its great impact on improving performance.